Menanamkan Karakter Religius Siswa Melalui Buku Ajar Tematik Terintegrasi PAI dan Budi Pekerti - Sulistyowati, Sulistyowati (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2017)
Textbook is one of learning components that plays an important role in determining the success of learning. Textbook as a media and one of main resources in the learning process has a strategic role to be developed to improve the quality of learning and cultivate religiosity of the students. The cultivation of religious characters will be effective, efficient, and interesting if the available textbooks are combined with the Islamic education and characters contents. Those contents will create religious atmosphere and familiarize the students in practising their religiosity in everyday life. In this way, the competency of Islamic education and characters are combined with the competency of other subjects that are packaged in a learning experience. Thus the Islamic values will be formed in students characters.